2018
DOI: 10.24920/11815
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Protein UNR Promotes Glioma Cell Migration and Regulates the Expression of Ribosomal Protein L9

Abstract: Objective To investigate the role of RNA binding protein─upstream-of-N-Ras (UNR) in the development of glioma and its molecular mechanism.Methods First, bioinformatics analysis of CGGA database was performed to detect UNR expression level and prognosis of patients with glioma. Western blot and real-time PCR were used to detect UNR expression level in glioma cell lines and tissues. Next, UNR siRNAs were transfected in glioma cells, and MTS assay and scratch wound-healing assay were used to detect changes in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In pathway enrichment analysis for up regulated genes was performed. Enriched genes such as SOD2 [68], RPS11 [69], RPL9 [70], MYC (MYC proto-oncogene, bHLH transcription factor) [71], SEC61G [72], BIRC5 [73], NEK2 [74], CDK2 [75], AURKB (aurora kinase B) [76], RPS3 [77], MGP (matrix Gla protein) [78], AEBP1 [79], CTHRC1 [80], COL1A1 [81], COL3A1 [82], TNC (tenascin C) [83], POSTN (periostin) [84], IGFBP2 [85], IGFBP3 [86], IGFBP4 [87], SRPX2 [88], LAMB1 [89], ESM1 [90], TGFBI (transforming growth factor beta induced) [91], ITGA5 [92], RAP1B [93], CAV1 [94], HMOX1 [95] and LOX (lysyl oxidase) [96] were linked with progression of GBM. GPX7 was important for advancement of gastric cancer [97], but this gene was identified first time in GBM and may be liable for progression of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…In pathway enrichment analysis for up regulated genes was performed. Enriched genes such as SOD2 [68], RPS11 [69], RPL9 [70], MYC (MYC proto-oncogene, bHLH transcription factor) [71], SEC61G [72], BIRC5 [73], NEK2 [74], CDK2 [75], AURKB (aurora kinase B) [76], RPS3 [77], MGP (matrix Gla protein) [78], AEBP1 [79], CTHRC1 [80], COL1A1 [81], COL3A1 [82], TNC (tenascin C) [83], POSTN (periostin) [84], IGFBP2 [85], IGFBP3 [86], IGFBP4 [87], SRPX2 [88], LAMB1 [89], ESM1 [90], TGFBI (transforming growth factor beta induced) [91], ITGA5 [92], RAP1B [93], CAV1 [94], HMOX1 [95] and LOX (lysyl oxidase) [96] were linked with progression of GBM. GPX7 was important for advancement of gastric cancer [97], but this gene was identified first time in GBM and may be liable for progression of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…The CSDE1 mRNA expression level was also higher in grade IV glioma than it was in grade II and III patients (P < 0.001) according to the data released by the Chinese Glioma Genome Atlas (CGGA). In addition, higher CSDE1 expression was correlated with poorer survival in glioma patients (P = 0.0177) [16]. Another recent investigation revealed that low CSDE1 expression was significantly associated with poor outcome in low-grade resected PDAC patients [20].…”
Section: Cancersmentioning
confidence: 97%
“…Oncogene [16] Breast cancer Oncogene [17] PCCs &PGLs Tumor suppressor [18] Oral squamous cell carcinoma Tumor suppressor [19] Pancreatic ductal adenocarcinoma Prognostic biomarker [20] Epithelial ovarian cancer Platinum resistance gene [21] Other diseases…”
Section: Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…VIM, RAC1) (Wurth et al, 2016). While the oncogenic potential of CSDE1 has been observed in multiple other tumors (Fang et al, 2005; Liu et al, 2020; Martinez-Useros et al, 2019; Tian et al, 2018), loss of function CSDE1 mutations have been detected in neuroendocrine tumors, suggesting tumor suppressive roles (Fishbein et al, 2017). Intrigued by context-specific functions of CSDE1 in cancer, we noticed that this RBP could bind SASP factor mRNAs in melanoma, although such binding did not have functional consequences in this system (Wurth et al, 2016).…”
Section: Introductionmentioning
confidence: 99%